Leadership experiences of undergraduate Muslim student leaders: an exploratory case study - Guimba, Wardah; Hashim, Che Noraini; Hussien, Suhailah; Razikin, Mohyani; Esteban, Ivie (EuroJournals Publishing, Inc., 2011)
Islamic institutions of higher learning are keeping abreast in developing their students for future leadership. However, few empirical investigations have been conducted thus giving impetus to this research. The main purpose of this study is to explore the leadership experiences and practices of undergraduate student leaders on their involvement as student government (SG) leaders at two Islamic institutions of higher learning in Marawi City, Philippines. Specifically, the objective of this study is to explore the student leaders’ understanding of the concept of leadership. Using the exploratory case study, the data were collected from small group discussions (SGD) consisting of six student leaders. Based on the results of the SGDs, the student participants viewed that their student government (SG)experiences assisted them in gaining self-confidence, interpersonal skills, communication skills, and civic consciousness. Moreover, the student leaders articulated that leadership could be divided into four constructs of themes, namely, defining leadership, motivating factors, constructing identity, and enhancing skills.